KEPADATAN NYAMUK DEWASA Aedes Sp DI KELURAHAN MALALAYANG I KECAMATAN MALALAYANG MANADO PERIODE JANUARI – PEBRUARI 2010 - Bernadus, Janno B. B.; Pijoh, Victor D.; Kareth, Venny (UNIVERSITAS SAM RATULANGI, 2011)
Abstract: Dengue Hemorrhagic Fever (DHF) has become a public health problem in Indonesia because of its high prevalence and ability to spread more widely. In North Sulawesi itself Case Fatality Rate of carrying dengue is increasing from year to year. The local village Malalayang has a high potential for spreading this disease. The result of an entomology survey on adult mosquitos showed that Aedes sp was found in 40 houses of 80 house samples. From these 40 houses we got 71 mosquito samples. From these 71 samples tested and identified, we found three species: Aedes aegypti (30 samples, 42.25%), Aedes albopictus (22 samples, 30.99%), and Culex sp (19 samples, 26.76%). Mosquito density can be seen from the indices of the resting rates, which were 0.375 for Aedes aegypti, 0.275 for Aedes albopictus, and 0.65 for Aedes sp. Key words: density, adult mosquito, Aedes sp., resting rate. Abstrak: Demam Berdarah Dengue (DBD) merupakan penyakit yang menjadi masalah kesehatan masyarakat di Indonesia karena prevalensinya yang tinggi dan penyebarannya semakin luas. Di Sulawesi Utara, Case Fatality Rate penyakit DBD tercatat terus meningkat dari tahun ke tahun. Kelurahan Malalayang I merupakan daerah yang potensial sebagai daerah penyebaran DBD. Survei entomologi terhadap nyamuk dewasa Aedes sp pada 80 rumah memperlihatkan bahwa 40 diantaranya terdapat 71 sampel nyamuk. Setelah diperiksa dan diidentifikasi ternyata ditemukan tiga spesies yaitu Aedes aegypti 30 sampel (42,25%), Aedes albopictus 22 sampel (30,99%) dan Culex sp 19 (26,76%). Kepadatan nyamuk dapat dilihat dari angka indeks pada resting rate yaitu Aedes aegypti = 0,375 , Aedes albopictus = 0,275 dan Aedes sp.= 0,65. Kata kunci: kepadatan, nyamuk dewasa, Aedes sp., resting rate.